Social Impact of Recharging Activity in Long-Term HRI and Verbal Strategies to Manage User Expectations During Recharge - Deshmukh, Amol; Lohan, Katrin Solveig; Rajendran, Gnanathusharan; Aylett, Ruth (Frontiers in Robotics and AI, 2018)
Social robots perform tasks to help humans in their daily activities. However, if they fail to fulfil expectations this may affect their acceptance. This work investigates the service degradation caused by recharging, during which the robot is socially inactive. We describe two studies conducted in an ecologically valid office environment. In the first long-term study (three weeks), we investigated the service degradation caused by the recharging behaviour of a social robot. In the second study, we explored the social strategies used to manage users’ expectations during recharge. Our findings suggest that the use of verbal strategies (transparency, apology, politeness) may make robots more acceptable to users during recharge.